Pathological Connections between Nonalcoholic Fatty Liver Disease and Chronic Kidney Disease - Huixia Liu; Chun Zhang; Jing Xiong (Karger Publishers, 2022)
Background: Nonalcoholic fatty liver disease and chronic kidney disease are major public health issues worldwide. The clinical burden of nonalcoholic fatty liver disease is not only confined to liver-related morbidity and mortality, but it also includes the burden of chronic extrahepatic complications. It is well known that liver and kidney are strictly interconnected in physiological and pathological conditions. Summary: Mounting evidence indicates a strong association between nonalcoholic fatty liver disease and chronic kidney disease, independent of the identified cardiorenal risk factors. The presence and severity of nonalcoholic fatty liver disease are related to the developmental stage and risk of chronic kidney disease. And chronic kidney disease progression also contributes to nonalcoholic fatty liver disease development. Nonalcoholic fatty liver disease and chronic kidney disease mutually contribute to disease progression through pathological links. Shared pathogenic mechanisms also exist between nonalcoholic fatty liver disease and chronic kidney disease, including pyroptosis and ferroptosis. Additionally, the use of combined liver-kidney transplantation has increased exponentially in recent years. Key Messages: This review focuses on the emerging pathological mechanisms linking nonalcoholic fatty liver disease and chronic kidney disease and shared pathogenic mechanisms to find novel targeted therapies and retard the progression of both disease processes.